Who is Still Haunted by the Specter of Communism? : Explaining Relative Output Contractions Under Transition - Elborgh-Woytek, Katrin (IMF Working Papers; Working Paper ;, 2005)
The paper analyzes the initial output decline in transition economies by estimating a crosssection model stressing two major factors-conflicts and the legacies of the Soviet period. We link the Soviet legacies in place at the outset of the transition to the subsequent path for the development of market-related institutions. Institutional development (as proxied by measures of corruption) is used as an intermediate variable. An instrumental variable approach is followed to derive estimates that are not biased by the possible endogeneity of corruption with respect to output developments. Assuming that the extent of Soviet legacies was positively correlated with the length of the communist rule allows us to use the years under the Soviet regime as an instrument.